Reconstructing the oxygen depth profile in the Arabian Sea during the last glacial period - Lu, Wanyi; Costa, Kassandra M; Oppo, Delia W (PANGAEA, 2023)
A total of six core sites of western Arabian Sea were selected to form a depth transect with water depths ranging from 600 to 3650 m, in order to reconstruct the oxygen depth profile in the Arabian Sea during the last glacial period. Four RC27 cores were sampled from the Lamont-Doherty Core Repository, and two TN041/047 cores were sampled from the Woods Hole Oceanographic Institution (WHOI) Seafloor Samples Repository. Sampling intervals were every 5 or 10 cm. All cores were dated to last ~30 thousand years. All samples were first freeze-dried, then wet-sieved to > 63 µm fraction with de-ionized water, and oven-dried at 45°C. Benthic foraminifera Cibicidoides spp. and Globobulimina affinis were picked from the > 212 µm fraction. Photos of benthic foraminifera were taken using a Scanning Electron Microscope (SEM) (Hitachi model TM3000) at WHOI. Benthic surface porosity was determined from the SEM photos. Benthic foraminifera carbon and oxygen isotopic analyses were made using a Finnigan MAT253 mass spectrometer at WHOI.
Keywords: Arabian Sea; Glacial; Oxygen; Paleoceanography